Kinematic Analysis of Fault-Slip Data in the Central Range of Papua, Indonesia - Sapiie, Benyamin (Geological Agency, 2016)
DOI:10.17014/ijog.3.1.1-16Most of the Cenozoic tectonic evolution in New Guinea is a result of obliquely convergent motion that ledto an arc-continent collision between the Australian and Pacific Plates. The Gunung Bijih (Ertsberg) Mining District(GBMD) is located in the Central Range of Papua, in the western half of the island of New Guinea. This study presentsthe results of detailed structural mapping concentrated on analyzing fault-slip data along a 15-km traverse of theHeavy Equipment Access Trail (HEAT) and the Grasberg mine access road, providing new information concerning thedeformation in the GBMD and the Cenozoic structural evolution of the Central Range. Structural analysis indicatesthat two distinct stages of deformation have occurred since 12 Ma. The first stage generated a series of en-echelonNW-trending (Ï-fold axis = 300Â°) folds and a few reverse faults. The second stage resulted in a significant left-lateralstrike-slip faulting sub-parallel to the regional strike of upturned bedding. Kinematic analysis reveals that the areasbetween the major strike-slip faults form structural domains that are remarkably uniform in character. The changein deformation styles from contractional to a strike-slip offset is explained as a result from a change in the relativeplate motion between the Pacific and Australian Plates at 4 Ma. From 4 - 2 Ma, transform motion along an 270Â°trend caused a left-lateral strike-slip offset, and reactivated portions of pre-existing reverse faults. This action had aprofound effect on magma emplacement and hydrothermal activity.